Ameloblastoma of the jaws: a retrospective analysis of 340 cases in a Malaysian population - Siar, Chong Huat; Lau, Shin Hin; Ng, Kok Han (Elsevier, 2012)
Purpose: Ameloblastoma of the human jaw is an uncommon but clinically significant odontogenic epithelial neoplasm. The aim was to analyze the clinicopathologic characteristics of ameloblastoma in a Malaysian population.